2023
DOI: 10.1002/cncy.22738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of anal cytology and high‐risk HPV genotyping for detecting anal HSIL in a clinic‐based sample of people living with and without HIV in Puerto Rico

Abstract: BackgroundGiven the disproportionately elevated anal cancer risk in high‐risk populations, it is important to assess the performance of commonly used anal cancer screening tools to improve the effectiveness of detection and treatment methods. This study evaluates 1) the concordance between anal cytology and histology results and 2) the performance of cytology and high‐risk human papillomavirus (HR‐HPV) genotyping as screening tools for detecting histologically confirmed anal high‐grade squamous intraepithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Detection of multiple infections decreased from VaIN2 (30.3%) to VaIN3 (18.4%), suggesting that selection of the most carcinogenic HPV genotypes has occurred, along with clearance of the least carcinogenic ones during the oncogenic process 13 . This is in line with other reports, 10,12 and also with other HPV‐related intraepithelial neoplasms and cancers such as vulva and anus 14–16 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Detection of multiple infections decreased from VaIN2 (30.3%) to VaIN3 (18.4%), suggesting that selection of the most carcinogenic HPV genotypes has occurred, along with clearance of the least carcinogenic ones during the oncogenic process 13 . This is in line with other reports, 10,12 and also with other HPV‐related intraepithelial neoplasms and cancers such as vulva and anus 14–16 …”
Section: Discussionsupporting
confidence: 88%
“…13 This is in line with other reports, 10,12 and also with other HPV-related intraepithelial neoplasms and cancers such as vulva and anus. [14][15][16] Since one of the HPV types included in the HPV 9-valent vaccine was present in 70.2% of VaIN2/3 cases, these lesions could have been likely prevented by 9-HPV vaccination, underlying the importance of this intervention in appropriate age. Recent cohort studies from Denmark 17 indicated that VaIN incidence decreased significantly after 2006 among women under 30 years of age, with an annual decrease of almost 16% per year, that is after HPV vaccine approval.…”
Section: Resultsmentioning
confidence: 99%